UFW organizers performing in celebration of the signing of the California Agricultural Labor Relations Act, 1975 - Manuel Echavarria::::::photographer::: (1975)
Years of struggle are rewarded in 1975. Veteran UFW organizers Jessica Govea, far right, and Eugenio (Winnie) Arvallo, left, perform in the Guadalupe Recreation Center to celebrate Governor Jerry Brown's signing of the California Agricultural Labor Relations Act into law. The act allows farm workers to vote and select the union of their choice, and UFW organizers to walk into the fields to talk to farm workers during specified break periods: a right enjoyed by industrial workers.